Estimating the Effects of Trade Policy - Robert Feenstra (University of California, Department of Economics, 1995)
This paper reviews empirical methods used to estimate the impact of trade policies under imperfect competition. We decompose the welfare effects of trade policy into four possible channels: (i) a deadweight loss from distorting consumption and production decisions; (ii) a possible gain from improving the terms of trade; (iii) a gain or loss due to changes in the scale of firms; and, (iv) a gain or loss from shifting profits between countries. For each channel, we discuss the appropriate empirical methods to determine the sign or magnitude of the effect, and illustrate the results using recent studies. Two other channels by which trade policy affects social or individual welfare - through changes in wages and changes in product variety - are discussed more briefly. Recent developments in the analysis of trade policies under perfectly competition are also reviewed.
Keywords: 330